Knowledge, Attitude and Practices of Psychiatric Nurses towards the Use of Physical Restraints in a tertiary care hospital Lahore, Pakistan - Hina Aslam, Tahira Shoukat, Sidra Shumshir Ali, Shama Tanveer. Aqsa Aslam, Saba Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The use of physical restraints for patients’ safety and to reduce the interference in treatment is common in psychiatric hospitals. In Psychiatric hospitals, Physical restraint is viewed as a simple solution to maintain patient comfort and safety. Physical restraint is always accompanied by risk of complications but correct application of physical restraints is a central nursing responsibility for patients who are temporarily incapacitated. Objective: To determine the knowledge, attitude and practices of staff nurses regarding the use physical restraints. Methodology: A descriptive cross sectional study design was used to achieve the study objective. The present study was carried out among psychiatric nurses at Punjab institute of mental Health, Lahore during month of January 2022 to March 2022.A convenient sample of 150 nurses who were working in the previously mentioned setting was included. In data collection a structured demographic questionnaire and predesigned questionnaire on level of Knowledge, Attitude and Practices of staff Nurses regarding Physical Restraints was used. Results: The staff nurses mean age was 27.86±3.55 years and mean experience (years) was 4.80±2.53. The mean standard deviation of level of knowledge, attitude & practices of physical restraints scale was 7.01±0.89, 35.04±3.62 and 36.26±1.54 among the respondents respectively. Knowledge and attitude was insignificant with sociodemographic and other factors (p-value >0.05), whereas practices were found significant with gender, marital status, special course attended as well as previous training acquired (p-value <0.05). Conclusion: The study concluded that knowledge of Psychiatric nurses in relation to the use of physical restraints was better, attitude of staff nurses was positive regarding use of physical restraints and staff nurses have reflection of better knowledge and positive attitude into their practices largely. Moreover, the practices among the nurses were significantly associated among gender of the nurses, marital status, special course attended and previously any physical restraint training was done. All of the scores had shown weak positive correlation with each other.